A Black Mineral Amulet from Colchester's North Cemetery. (November 2020) - Crummy, Nina; Davis, Glynn J.C.
ABSTRACT: A black mineral amulet in the form of a human bust is the only one of its kind so far found in Britain. Found c. 1900 during brick-making, it probably came from the burial of a young female. The authenticity of its provenance, context and associated finds is reviewed in the light of other grave groups, and its iconography and use are compared to those of other black mineral amulets from Britain and the Continent. Supplementary material available online (https://doi.org/10.1017/S0068113X20000094 ) comprises a short biography of Henry Money and a catalogue of beads.